Measurement of the polarization of the Υ(1S) and Υ(2S) states in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2008)
We present a study of the polarization of the Υ(1S) and Υ(2S) states using a 1.3fb-1 data sample collected by the D0 experiment in 2002-2006 during run II of the Fermilab Tevatron Collider. We measure the polarization parameter α=(σT-2σL)/(σT+2σL), where σT and σL are the transversely and longitudinally polarized components of the production cross section, as a function of the transverse momentum (pTΥ) for the Υ(1S) and Υ(2S). Significant pTΥ-dependent longitudinal polarization is observed for the Υ(1S). A comparison with theoretical models is presented. © 2008 The American Physical Society.